Approche dialogique d’une interview politique télévisée - Virginie Delmas (Communication)
This article sets out to show how and in what manner Bakhtin’s concept of dialogism, and some of its features (interdiscourse, reported discourse, etc.), can reveal the strategies carried out by interlocutors in a televised political interview.